Implementation of a prebirth bovine alarm for Finca Jaicar - Hidalgo-Arias, Josué (2019)
In this article is presented the design and implementation of a prototype made to detect patrons on the typical movements of cows that are going to give birth soon, and with that is generated an alarm. Also shows the contractions detector algorithm, that uses the angles of pitch, warp and yaw to elaborate an estimation on the giving birth.